2012
DOI: 10.1371/journal.pone.0032548
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Preliminary Analysis of Crystals of the 24-Meric Hemocyanin of the Emperor Scorpion (Pandinus imperator)

Abstract: Hemocyanins are giant oxygen transport proteins found in the hemolymph of several invertebrate phyla. They constitute giant multimeric molecules whose size range up to that of cell organelles such as ribosomes or even small viruses. Oxygen is reversibly bound by hemocyanins at binuclear copper centers. Subunit interactions within the multisubunit hemocyanin complex lead to diverse allosteric effects such as the highest cooperativity for oxygen binding found in nature. Crystal structures of a native hemocyanin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Recently studies suggested that Tachylectins plays an important role as pattern recognition molecules in the innate immune response system and blood coagulation ((Gokudan et al, 1999). Homocyanins, a large copper-binding metalloproteins in the hemolymph of invertebrates, acts as a respiratory pigment in the transport of oxygen and responsible for the blue coloration of arthropods hemolymph (Hosseinzadeh et al, 2019;Jaenicke et al, 2012). The present studies showed that, even though the levels of Hemocyanin mRNA were found in all samples but the highest level of Hemocyanin mRNA expression occurred in the adult scorpions.…”
Section: Othersupporting
confidence: 42%
See 1 more Smart Citation
“…Recently studies suggested that Tachylectins plays an important role as pattern recognition molecules in the innate immune response system and blood coagulation ((Gokudan et al, 1999). Homocyanins, a large copper-binding metalloproteins in the hemolymph of invertebrates, acts as a respiratory pigment in the transport of oxygen and responsible for the blue coloration of arthropods hemolymph (Hosseinzadeh et al, 2019;Jaenicke et al, 2012). The present studies showed that, even though the levels of Hemocyanin mRNA were found in all samples but the highest level of Hemocyanin mRNA expression occurred in the adult scorpions.…”
Section: Othersupporting
confidence: 42%
“…region or in the visible range of the spectrum (Padmanabhanaidu, 1966). Although, the preliminary studies on the physiological properties and structural of the Haemocyanin in scorpions has been con rmed the respiratory and also buffering function of Haemocyanin (Padmanabhanaidu, 1966;Jaenicke et al, 2012), none of them has been compared the expression of Homocyanin in adult and juvenile scorpions and this issue needs further investigation.…”
Section: Othermentioning
confidence: 99%
“…Hemocyanins (HCNs) are large type-3 metalloproteins that transport oxygen in the blood of invertebrates like arthropods and molluscs ( Van Holde and Miller, 1995 ; Terwilliger, 1998 ; Burmester, 2002 ; Pick et al, 2008 ; Rehm et al, 2012 ; Marxen et al, 2014 ; Pinnow et al, 2016 ). Their binuclear active site coordinates copper as metal and accommodates oxygen as a peroxide ion, due to which copper oxidizes from (I) to (II) oxidation state ( Himmelwright et al, 1978 , 1980 ; Magnus and Ton-That, 1991 ; Jaenicke et al, 2012 ). Besides oxygen transportation, they have also been found to play a major role in diverse physiological functions like homeostasis, transportation of hormones ( Prosser and Brown, 1961 ), in the development of immunity via activation of phenoloxidases protein that plays a major role in the formation of their exoskeleton formation and melamine pigments, as well as wound recovery ( Lei et al, 2008 ; Coates et al, 2011 ; Coates and Nairn, 2014 ; Zhong et al, 2016 ; Coates and Talbot, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a method that could provide microscopic insights into the dynamic behavior of the HCNs and variations as a function of time needs to be employed. Many experimental studies have been reported for HCNs (Decker et al, 1988;Volbeda and Hol, 1989;Magnus and Ton-That, 1991;Hazes et al, 1993;Magnus et al, 1994;Jaenicke et al, 2012;Saito and Thiel, 2014;Naresh et al, 2015Naresh et al, , 2015Bux et al, 2018). Most of the up-to-date work commonly discusses the structural features of protein in its monomeric form and rarely in its biologically active hexameric form (Volbeda and Hol, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…70-75 kDa) consists of three domains: domain I contains five to six α-helices, domain II contains a four α-helix bundle and domain III is a seven stranded anti-parallel β-barrel. Domain II also encompasses the di-copper centre [14,[28][29][30][31][32]. The geometry and coordination environment of the active site of the arthropod PO are very similar to those of the arthropod Hc; and while not all POs are hexameric [33], those from crustaceans are [34,35].…”
Section: Introductionmentioning
confidence: 99%